CETP TaqIB polymorphism in Turkish adults: association with dyslipidemia and metabolic syndrome - Oezsait, Bilge; Koemuercue-Bayrak, Evrim; Poda, Mehves; Can, Guenay; Hergenc, Guelay; Onat, Allan; Humphries, Sleve E.; Erginel-Uenaltuna, Nihan (TURKISH SOC CARDIOLOGY, 2008)
Objective: In this study, our aim was to investigate the association of cholesterol ester transfer protein (CETP) TaqIB polymorphism with the likelihood of metabolic syndrome (MetS). Methods: Study was designed as a cross-sectional analysis of the Turkish Adult Risk Factor follow-up study. Randomly selected sample of 1585 persons were included in the analyses. Genomic DNAs were isolated and the genotyping was performed using TaqMan system. ANOVA, Chi-square, univariate analyses and logistic regression models were used to investigate the association of genotypes with clinical and biochemical measurements. Results: The frequencies of the B1B1, B1B2 and the B2B2 genotypes were 33.3%, 46.4% and 20.3%, respectively. The B2B2 genotype was associated with elevated high-density lipoprotein -cholesterol (HDL-C) levels (p<0.0001). After adjusting for sex and age 132132 individuals had 15.9% higher HDL-C levels than 131131 individuals. Furthermore, the likelihood of dyslipidemia was lower in the presence of the B2B2 genotype (30.9% non-dyslipidemic vs. 69.1% dyslipidemic, p=0.001) when compared to the other genotypes. Moreover, in a logistic regression model comprising age and environmental factors, 131 allele carriers showed higher odds ratios of 1.49 (OR=1.49, 95% CI; 1.03-2.14, p=0.032) for MetS only in females. Conclusions: These results suggest that 131 allele is associated with MetS in adult females. However, TaqIB polymorphism appears not associated with the components of MetS other than atherogenic dyslipidemia in adult Turkish population. (Anadolu Kardiyol Derg 2008; 8: 324-30)
Keywords: CETP TaqIB; metabolic syndrome; dyslipidemia; HDL cholesterol; Turkish adults; logistic regression analysis; ESTER TRANSFER PROTEIN; HIGH-DENSITY-LIPOPROTEIN; CHOLESTEROL LEVELS; CARDIOVASCULAR RISK; HDL-CHOLESTEROL; GENE; DISEASE; DEFINITION; SMOKING; Cardiovascular System & Cardiology